PHYTOCHEMICAL AND PHARMACOLOGICAL REVIEW OF ETHNO MEDICINAL PLANT: JATROPHA CURCAS L. - Dr. Nidhi Tyagi; Nitin Chaudhary (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Jatropha curcas (Family:Euphorbiaceae); Physic nut a drought-resistant shrub or tree, which is widely distributed in the wild or semi-cultivated areas in Central and South America, Africa, India and South East Asia. Jatropha curcas is a drought resistant, perennial plant that grows even in the marginal and poor soil. Raising Jatropha is easy. It keeps producing seeds for many years. In the recent years, Jatropha has become famous primarily for the production of biodiesel; besides this it has several medicinal applications.The Jatropha curcas L. plant is used as a medicinal plant such as seeds against constipation; sap for wound healing; leaves as tea against malaria etc.Seeds used to treat arthritis, gout and jaundice.Stem acts in toothache, gum inflammation, gum bleeding, pyorrhoea.Plant extract used in treatment of allergies, burns, cuts and wounds, inflammation, leprosy, leucoderma, scabies and small pox.Water extract of branches is used in Human immunodeficiency virus, tumour and Plant extract in wound healing. Plant sap in dermatomucosal diseases